Implementasi Kebijakan Bantuan Pasang Baru Listrik Di Sebagian Kabupaten Di Provinsi Bengkulu - Aji Umar Za; Triyuni Soemartono; Roy Tumpal Pakpahan (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Study purpose. This study focuses on the implementation of policies, obstacles, efforts, and forecasts made to optimise new electricity connection assistance policies in several districts in Bengkulu Province. The objectives of this study are to analyse the implementation of policies, obstacles, efforts, and forecasts made to optimise new electricity connection assistance policies in several districts in Bengkulu Province. Materials and Methods. The research method used in this study is a qualitative method with data collection techniques including observation, interviews, and documentation. The data obtained will be analysed through data collection, data reduction, data presentation, and conclusion drawing. The theory used is Results. Based on the data and analysis conducted, it can be concluded that the implementation of new electricity connection assistance in some districts in Bengkulu Province can be seen from the following findings: (1) The implementation of new electricity connection assistance in some districts in Bengkulu Province is in line with the results of the discussion by the Desk for Government Affairs in the Energy and Mineral Resources Sector at the Technical Coordination Meeting on Development Planning for 2024, conducted by the Directorate General of Regional Development at the Ministry of Home Affairs. (2) Challenges in the implementation of new electricity connection assistance in certain districts of Bengkulu Province include discrepancies between the proposals submitted by the community and the actual conditions on the ground, as well as the fact that the homes of the proposing community are located outside the reach of PLN's electricity network. (3) Efforts needed to optimise the implementation of new electricity connection assistance in some districts in Bengkulu Province include socialising the new electricity connection assistance to underprivileged communities. (4) Looking ahead, with electricity reaching even the remotest villages, it is hoped that communities that have received new electricity connection assistance will utilise the assistance effectively, such as by using it to establish small and medium enterprises (SMEs) that can serve as additional income sources for those communities. Conclusion. The implementation of new electricity connection assistance in some districts in Bengkulu Province has been progressing fairly well, although it still faces challenges in coordination and network coverage, and requires improved socialisation and data synchronisation to support more productive use of electricity for the welfare of the community.